Levodopa/Benserazide PLGA Microsphere Prevents L-Dopa–Induced Dyskinesia via Lower β-Arrestin2 in 6-Hydroxydopamine Parkinson’s Rats - Wang, Wen-Wen; Zhang, Xing-Ru; Lin, Jing-Ya; Zhang, Zeng-Rui; Wang, Zhen; Chen, Si-Yan; Xie, Cheng-Long (Frontiers in Pharmacology, 2019)
Prolonged pulsatile administration of Levodopa (L-dopa) can generate L-dopa–induced dyskinesia (LID). Numerous studies have shown that continuous dopamine delivery (CDD) was helpful in reducing the expression of LID. 6-OHDA lesioned rats were randomly divided into two groups to receive intermittent L-dopa stimulation (L-dopa/benserazide) or Levodopa/benserazide PLGA microsphere (LBPM) for 3 weeks. rAAV (recombinant adeno-associated virus) vector were used to overexpress and ablation of β-arrestin2. We found that LBPM developed less AIM severity compared with standard L-dopa administration, whereas selective deletion of β-arrestin2 in striatum neurons dramatically enhanced the severity of dyskinesia by LBPM. On the contrary, the effects of LBPM in terms of ALO AIM was further relieved by β-arrestin2 overexpression. Furthermore, no significant change in motor behavior were seen neither in inhibition nor overexpression of β-arrestin2. In short, our experiments provided evidence that LBPM prevented LID behavior was likely to through β-arrestin2, suggesting that a therapy modulating β-arrestin2 may provide a more effective anti-dyskinetic approach with a low risk of untoward effects.